Assessing individual performance in team sports: A new method developed in youth volleyball - Bisagno, E.; Morra, S.; Basciano, M.; Rosina, C.; Vitali, F. (Journal of Functional Morphology and Kinesiology, 2019)
Studying the role of individual differences in team sports performance is a challenge. The main problem is having an available measure of individual performance of each member of the team. In particular, in youth sports, where the level of specialization is reactively low, it appears appropriate that this measure takes the entire performance of the athlete into consideration (i.e., that it assesses all of the athlete`s gestures), while maintaining an ecological validity criterion. Therefore, we devised and calculated an individual assessment measure in volleyball following the subsequent steps: Firstly, we video-recorded at least three volleyball games for each of the 114 youth volleyball players who participated in the study. Then, two independent expert observers evaluated each individual performance by attributing a score to every single gesture performed by the athletes during the games. The derived individual score was adjusted and controlled for the team performance measure, namely the result of each Set the athlete participated in (and for the amount of participation of the athlete to each game). The final measure of individual performance in volleyball proved to be reliable, showing a high level of interrater agreement (r = .841, p < .001) and a significant correlation with the amount of experience in volleyball (r = .173, p < .05).